Exploring the influence of demographic factors on use of superstar learning App among college students in Liaoning province under second digital divide - QingHao Wu; Norhayati Mohd Yusof; Yuen Fook Chan (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This paper aims to explore the influence of demographic factors on the use of Superstar mobile learning apps among college students. It examines the differences in the frequency of usage of mobile learning apps among college students under second digital divide based on genders, household location registration, and major discipline. Hopefully, this study will provide policymakers in China an opportunity to identify factors that will affect the equal access to mobile learning apps among college students. This study can lead to the reduce of education and social inequality. This study adopts a quantitative method of survey using online questionnaire to collect data from college students of a private university in Liaoning Province. After the data has collected, the SPSS.26 was used to analyze the data using independent sample t-tests based on genders, household location registration, and major discipline to conduct the differentiation analysis.There was no significant difference identified in the frequency of usage of SuperStar Learning app among college students based on genders, household location registration or major discipline. However, science and technology students showed a greater dispersion in the frequency of usage of SuperStar Learning App compared to humanities and social science students. The study suggests that overall most of the college students have achieved moderate level of usage ability in the use of Superstar learning app, however the usage of Superstar learning app varied based on the demographic factors.The findings indicate that demographic factors did not have any influence on the use of Superstar Learning App among the college students. Hence, the university might not need to design the training programs based on demographic factors of the college students. This is encouraging from a digital equity perspective, as it shows that Superstar Learning App is able to be accessed and used by a broad group of students, regardless of their background.